2013
DOI: 10.1097/01.aids.0000432475.14992.da
|View full text |Cite
|
Sign up to set email alerts
|

Modelling HIV incidence and survival from age-specific seroprevalence after antiretroviral treatment scale-up in rural South Africa

Abstract: Objective:Our study uses sex-specific and age-specific HIV prevalence data from an ongoing population-based demographic and HIV survey to infer HIV incidence and survival in rural KwaZulu-Natal between 2003 and 2011, a period when antiretroviral treatment (ART) was rolled out on a large scale.Design:Catalytic mathematical model for estimating HIV incidence and differential survival in HIV-infected persons on multiple rounds of HIV seroprevalence.Methods:We evaluate trends of HIV incidence and survival by estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
2
32
1
Order By: Relevance
“…First, in this age-group, younger individuals are on average more likely to be infectious. As our data show for women (see Figure S4), and previous research has shown for both men and women [21], HIV incidence declines with age after 30 even though prevalence continues to rise. Since those with acute incident HIV are far more likely to transmit the disease per sex act [38], higher infection rates for younger partners may reflect this age-distribution of incidence.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…First, in this age-group, younger individuals are on average more likely to be infectious. As our data show for women (see Figure S4), and previous research has shown for both men and women [21], HIV incidence declines with age after 30 even though prevalence continues to rise. Since those with acute incident HIV are far more likely to transmit the disease per sex act [38], higher infection rates for younger partners may reflect this age-distribution of incidence.…”
Section: Discussionsupporting
confidence: 87%
“…This is despite the fact that HIV incidence remains a considerable concern in this age-range: in high-prevalence settings it been measured to be as high as 2% per year for women past their fortieth birthdays [21,22]. Indeed, female HIV incidence at older ages may even be increasing, as older men living with HIV are living and sexually active for longer due to increased ART availability [23], or older individuals remaining in the active sexual network for longer [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In VIRGO, recommended timeframe guidelines were exceeded in more women than men, particularly for the transfer patients (door-to-balloon >120 min: 67% vs 44%, P<0.001) 11 . Older age is a known independent predictor of achieving goal reperfusion time 13 , which suggests a delay in younger patients —a group that may be more susceptible to sex-differences 22 .…”
Section: Discussionmentioning
confidence: 99%
“…HIV transmission was represented through heterosexual contact influenced by mixing patterns and behavioral factors including condom use. The model was calibrated using Bayesian methods to longitudinal HIV incidence [13] and prevalence [14] data from KwaZulu-Natal and cross-sectional behavioral riskstratified HIV prevalence data from South Africa [15]. Model details are provided in the Supplementary Data.…”
Section: Model Designmentioning
confidence: 99%